Hands-On Generative AI: Applying Your Tabular Data With ChatGPT, GPT-4, and LangChain. - Zhang, Alina (linkedin.com, 2023)
Learn about the knowledge and skills to harness the potential of ChatGPT and other OpenAI models on tabular data.